Early detection : women, cancer, & awareness campaigns in the twentieth-century United States - Gardner, Kirsten E. (Kirsten Elizabeth) (University of North Carolina Press, 2006)
Aims to dispel the common notion that American women became activists in the fight against female cancer only after the 1970s. This book offers an examination of films, publications, health fairs, and archival materials and traces women's cancer education campaigns back to the early twentieth century.